The Implementation Of CRPD In Indonesia to Ensure Educational Rights For Autistic Children (Case Study: Makassar) - Culla, Adi Suryadi; Lawi, Annisa Fauziah; Cangara, Abdul Razaq; Marzaman, Atika Puspita (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Padjadjaran, 2024)
Stigma regarding people with autism is still developing in society. The impact limits the movement of people with autism in obtaining their rights, including the right to education. This article investigates the implementation of the Convention on The Rights of Persons with Disabilities (CRPD) as a regime to discourse the educational rights of children with autism in Makassar City. The study uses Grindle and Thomas's framework to evaluate policy design, conflict arena, and regime implementation resources. While regional laws demonstrate a joyous policy design, various actors such as the Mayor, City Council, Education Office, and the autism community play crucial roles in the arena of conflict. However, challenges persist in fulfilling technical and physical resources, restricting the practical success of UNCRPD implementation for autism education in Makassar City.